Android-Based Mobile Application Design for Booking Meeting Room Using Decision Making Method in Pt Kereta Api Indonesia (Persero) - Firmansyah, Gerry; Mohammad, Abel; Gautama, Hasyim.; Hasan Padmanegara, Oliver (International Journal of Psychosocial Rehabilitation, 2020)
Booking a meeting place is usually done by visiting the location directly or asking via telephone and it turns out that for the desired day is not available. This is very ineffective if the customer needs a meeting place in the near future and does not know any place that can be used for meetings and in accordance with the capacity of the desired person. The solution to make it easy to book a meeting place is in the form of the Meeting Room Booking application which is the research theme of this publication's text.This information system design method uses the SDLC (System Development Life Cycle) method in which there are requirements analysis stages, system design, system coding, system testing, and analysis.The feature given by the user is that the user can book a meeting place based on time, the desired place and the number of meeting attendees' capacity that can be done without the user having to reserve a location directly and get information on the availability of places that can still be used for meetings.Admins has been given admin’s website dashboard that is used to monitor incoming orders. By doing this research can facilitate a number of employees who want to book a meeting place quickly when an unexpected time or from a long distance away without having to review the location of the meeting. They can immediately determine the place as desired and determine the accommodating room with the number of meeting participants.